Duration of T4 Suppression in Hyperthyroid Cats Treated Once and Twice Daily with Transdermal Methimazole. (9th February 2013) - Boretti, F.S.; Sieber‐Ruckstuhl, N.S.; Schäfer, S.; Baumgartner, C.; Riond, B.; Hofmann‐Lehmann, R.; Reusch, C.E.
<x xml:space="preserve">Abstract</x> Background Transdermal methimazole is an acceptable alternative to oral treatment for hyperthyroid cats. There are, however, no studies evaluating the duration of T4 suppression after transdermal methimazole application. Such information would be valuable for therapeutic monitoring. Objective To assess variation in serum T4 concentration in hyperthyroid cats after once‐ and twice‐daily transdermal methimazole administration. Animals Twenty client‐owned cats with newly diagnosed hyperthyroidism. Methods Methimazole was formulated in a pluronic lecithin organogel‐based vehicle and applied to the pinna of the inner ear at a starting dose of 2.5 mg/cat q12h (BID group, 10 cats) and 5 mg/cat q24h (SID group, 10 cats). One and 3 weeks after starting treatment, T4 concentrations were measured immediately before and every 2 hours after gel application over a period of up to 10 hours. Results Significantly decreased T4 concentrations were observed in week 1 and 3 compared with pretreatment concentrations in both groups. All cats showed sustained suppression of T4 concentration during the 10‐hour period, and T4 concentrations immediately before the next methimazole treatment were not significantly different compared with any time point after application, either in the BID or SID groups. Conclusions Because transdermal methimazole application led to prolonged T4 suppression in both the BID and SID groups, timing of blood sampling does not seem to be critical when assessing treatment response.